2012
DOI: 10.1128/aac.00572-11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Effects of Coadministration of Lersivirine with Raltegravir or Maraviroc in Healthy Subjects

Abstract: Lersivirine (UK-453,061) is a new nonnucleoside reverse transcriptase inhibitor currently being developed as a treatment for human immunodeficiency virus type 1 infection. Lersivirine shows potent activity against wild-type and clinically relevant drugresistant strains. Previous studies have demonstrated that lersivirine is metabolized by glucuronidation via UGT2B7 and by cytochrome P450 3A4 (CYP3A4). Lersivirine is also a weak inducer of the CYP3A4 enzyme. Therefore, coadministered lersivirine could potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…15 Lersivirine is a weak CYP3A4 inducer, although its further development was stopped in 2013. 102 In healthy subjects given 300 mg MVC and 500 mg Lersivirine twice daily, MVC Cmax and AUC increased by 3.4% and 6.2%, respectively, compared to subjects given MVC plus placebo. 102 NVP increased MVC Cmax and AUC by 101% and 154%, respectively 99 ( Table 2 ).…”
Section: Mvc Drug–drug Interactionsmentioning
confidence: 96%
“…15 Lersivirine is a weak CYP3A4 inducer, although its further development was stopped in 2013. 102 In healthy subjects given 300 mg MVC and 500 mg Lersivirine twice daily, MVC Cmax and AUC increased by 3.4% and 6.2%, respectively, compared to subjects given MVC plus placebo. 102 NVP increased MVC Cmax and AUC by 101% and 154%, respectively 99 ( Table 2 ).…”
Section: Mvc Drug–drug Interactionsmentioning
confidence: 96%
“…No significant changes in lersivirine’s pharmacokinetic parameters were seen. The authors concluded that lersivirine and raltegravir could likely be co-administered without need for dose adjustments [25]. Additionally, the NNRTI rilprivirine was studied and also found to have little effect on the concentrations of raltegravir when used in combination [26].…”
Section: Raltegravirmentioning
confidence: 99%
“…A once daily fixed dose Quad regimen containing elvitegravir 150 mg/cobicistat 150 mg/emtricitabine 200 mg/ tenofovir 300 mg is currently in Phase 3 trials [25]. The Quad formulation has recently demonstrated 48 week non-inferiority in treatment naïve HIV-infected patients to atazanavir/ritonavir plus emtricitabine/tenofovir (90% vs. 87%, respectively) and to efavirenz/emtricitabine/tenofovir (88% vs. 84%, respectively ) in maintenance of viral RNA ≤ 50 copies/mL [57,58].…”
Section: Elvitegravirmentioning
confidence: 99%
“…Most studies investigated compounds acting on the innate immune system (19 studies) ( 20 – 38 ), followed by compounds with immunoregulatory activity, classified into immunomodulatory (cereblon [CRBN] modulators; 14 studies) ( 39 44 , 46 – 52 ) and mediators of immune cell functions (CCR5 antagonists; 14 studies) ( 54 59 , 61 63 , 65 67 , 76 ). All the other compounds were investigated in only one or two HV studies.…”
Section: Resultsmentioning
confidence: 99%